From complex gut communities to minimal microbiomes via cultivation. (August 2017) - Clavel, Thomas; Lagkouvardos, Ilias; Stecher, Bärbel
Graphical abstract: Highlights: Microbiome research will benefit from the complementary use of culture and molecular approaches. Cultured microbes do not represent a minority of human gut microbiota. Description and archiving of novel taxa is currently a bottleneck. Minimal microbiomes are useful tools that must be modular and easily accessible. Abstract : The mammalian gut microbiota is dominated by populations of bacteria, mostly strict anaerobes. Because these bacteria can influence the health of their host, it is important to investigate their diversity and functions, which can be done via culture-based or molecular approaches. In recent years, microbiologists have very often preferred the use of molecular techniques, as they do not limit the analysis to the fraction of communities that can be grown in the laboratory. In reality, cultivation and molecular methods are complementary, and we are now witnessing a period of unification. Obtaining strains that can be grown in vitro is currently indispensable for the description of novel diversity and eventually the improvement of taxonomic and sequence databases. Moreover, cultivation allows using host-specific minimal consortia of microbes that are helpful for detailed and standardized studies of gut microbial communities and microbe-host interactions. Molecular techniques are helpful because they can provide insights into strain-level diversity and the functional potential of organisms. Furthermore, genomic and metagenomic data allow inferring growth conditions for uncultured bacteria and also enable detailed genetic studies. In the present manuscript, we highlight recent work on culture-based investigation of mammalian gut bacteria and microbe-host interactions and give our opinions on challenges and perspectives in the field.